Lithium-rich manganese-based positive electrode precursor material, preparation method thereof, positive electrode material and battery
By designing a lithium-rich manganese-based positive electrode precursor material with core and shell structures, and using the continuous-batch method to prepare the lithium-rich manganese-based positive electrode material in practical applications, the performance problems of lithium-rich manganese-based positive electrode material in practical applications have been solved, and the electrochemistry has been improved Performance and structural stability effects.
Patent Information
- Application Number
- CN202411565835.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In practical applications, lithium-rich manganese-based positive electrode materials have problems such as low first charge and discharge efficiency, significant attenuation of voltage and capacity during cycles, and easy destruction of the material structure, which has led to its failure to be widely used.
By designing a lithium-rich manganese-based positive electrode precursor material, it consists of a core and a shell layer, which is formed by interlaced arrangement of sheet-shaped primary particles, and the shell layer is formed by radial arrangements perpendicular to the core surface along the diameter surface. , combined with the continuous-batch method preparation method, improve the structural strength and electrochemical properties of the material.
It has achieved the improvement of the electrochemical performance of lithium-rich manganese-based positive electrode material, enhanced the structural stability and cyclic performance of the material, and extended the cycle life and charge and discharge performance of lithium-ion batteries.
Smart Images

Figure CN119430323A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery materials, and in particular relates to a lithium-rich manganese-based positive electrode precursor material and a preparation method thereof, a positive electrode material and a battery. Background Art
[0002] Lithium-rich manganese-based cathode materials have good market prospects due to their high specific capacity, good thermal stability and cycle performance, wide charge and discharge voltage range and low cost. However, in actual production applications, lithium-rich manganese-based cathode materials have problems such as low initial charge and discharge efficiency, significant voltage and capacity attenuation during the cycle, and easy destruction of the material structure, which has prevented the material from being widely used.
[0003] In the preparation process of lithium-ion batteries, the process preparation conditions and physical and chemical properties of the precursor will have an important impact on the performance indicators of the positive electrode material. The physical properties of the lithium-manganese-rich positive electrode precursor material, such as structure and morphology, will continue to the lithium-manganese-rich positive electrode material and have a great impact on its electrochemical performance. Usually, lithium-manganese-rich precursor materials are mostly synthesized by co-precipitation, and the precursor primary particles prepared by this method are thin and have poor mechanical strength. The lithium-manganese-rich positive electrode material prepared therefrom is prone to structural collapse and inactivation under high-voltage charge and discharge conditions, which in turn leads to an increase in the impedance of the lithium-ion battery assembled therefrom, and poor cycle performance and rate performance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium-rich manganese-based positive electrode precursor material and a preparation method thereof, a positive electrode material and a battery, aiming to improve the particle morphology of the lithium-rich manganese-based precursor material and enhance its structural strength, thereby improving the electrochemical performance of the lithium-rich manganese-based positive electrode material.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a lithium-rich manganese-based positive electrode precursor material, which includes a core and a shell layer on the surface of the core; the core is formed by staggered arrangement of flaky primary particles, and the shell layer is formed by plate-like primary particles arranged radially along a radial surface perpendicular to the surface of the core.
[0007] In an optional embodiment, the core of the lithium-rich manganese-based positive electrode precursor material is nickel manganese hydroxide, with a chemical formula of Ni x Mn y (OH)2, the shell is a composite of nickel manganese hydroxide and nickel manganese borate, the chemical formula of the nickel manganese borate is (Ni x Mn y)3(BO3)2, where 0.2≤x≤0.4, 0.6≤y≤0.8, x+y=1.
[0008] In an optional embodiment, the porosity of the inner core of the lithium-rich manganese-based positive electrode precursor material is greater than the porosity of the shell layer.
[0009] In an optional embodiment, the thickness of the flaky primary particles in the lithium-rich manganese-based positive electrode precursor material is 0.04-0.11 μm, and the thickness of the plate-like primary particles is 0.1-0.3 μm.
[0010] In an optional embodiment, the porosity of the core in the lithium-rich manganese-based positive electrode precursor material is 8%-13%, and the porosity of the shell is 1%-5%.
[0011] In an optional embodiment, in the lithium-rich manganese-based positive electrode precursor material, the diameter of the core is 1.5-4 μm, and the thickness of the shell is 1-3 μm.
[0012] In an optional embodiment, the median particle size Dv50 of the lithium-rich manganese-based positive electrode precursor material is 3-7 μm.
[0013] In an optional embodiment, the mass percentage of boron element in the lithium-rich manganese-based positive electrode precursor material is 0.03%-0.2%.
[0014] In an optional embodiment, the tap density of the lithium-rich manganese-based positive electrode precursor material is 1.5-2.0 g / cm 3 .
[0015] In an optional embodiment, the specific surface area of the lithium-rich manganese-based positive electrode precursor material is 12-20 m 2 / g.
[0016] In a second aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode precursor material, the preparation method comprising the following steps: preparing a first slurry containing nickel manganese hydroxide particles; preparing a mixed solution containing nickel, manganese and boron; The mixed solution, the first precipitant solution and the first ammonia water are added in parallel to the reactor containing the first slurry to carry out a first co-precipitation reaction, and the concentrator is turned on for concentration. When the particle size Dv50 of the particles in the reactor reaches 3-7 μm, the liquid feeding is stopped to obtain a second slurry; the second slurry is subjected to solid-liquid separation, washing, drying and sieving to obtain a lithium-rich manganese-based positive electrode precursor material.
[0017] In an optional embodiment, the mixed solution is obtained by mixing a first nickel-manganese mixed salt solution with a boron source solution, the concentration of the boron source solution is 0.1-2 mol / L; the boron source includes at least one of boric acid, sodium borate and ammonium borate.
[0018] In an optional embodiment, the mass of the boron source in the mixed solution is 0.2%-1% of the theoretical yield of nickel manganese hydroxide in the lithium-rich manganese-based positive electrode precursor material.
[0019] In an optional embodiment, the reaction temperature of the first coprecipitation reaction is 45-60°C, the reaction pH is 9.5-10.5, and the ammonia concentration during the reaction is 1.5-4.5 g / L.
[0020] In an optional embodiment, continuous stirring is required during the first coprecipitation reaction, and the stirring speed is 300-450 r / min.
[0021] In an optional embodiment, the mixed solution is added to the reactor at a flow rate of 2-4 L / h.
[0022] In an optional embodiment, the preparation step of the first slurry includes introducing an inert gas into a reactor containing pure water and starting stirring, adding a second nickel-manganese mixed salt solution, a second precipitant solution and a second ammonia water into the reactor in parallel to carry out a second co-precipitation reaction, and stopping the liquid feeding when the particle size Dv50 of the particles in the reactor reaches 1.5-4 μm to obtain a first slurry containing nickel-manganese hydroxide particles.
[0023] In an optional embodiment, the nickel salt in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution includes at least one of nickel sulfate, nickel chloride and nickel nitrate, and the manganese salt includes at least one of manganese sulfate, manganese chloride and manganese nitrate.
[0024] In an optional embodiment, the molar concentration of the metal element in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution is 0.5-2.5 mol / L.
[0025] In an optional embodiment, the molar ratio of nickel element to manganese element in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution is (0.2-0.4): (0.6-0.8).
[0026] In an optional embodiment, the first precipitant solution and the second precipitant solution are sodium hydroxide solutions or potassium hydroxide solutions with a molar concentration of 6-12 mol / L.
[0027] In an optional embodiment, the molar concentration of the first ammonia water and the second ammonia water is 0.5-2 mol / L.
[0028] In an optional embodiment, the inert gas is nitrogen, and the nitrogen flow rate is 5-30 L / min.
[0029] In an optional embodiment, the stirring speed is 450-600r / min.
[0030] In an optional embodiment, the reaction temperature of the second coprecipitation reaction is 35-45°C, the reaction pH is 10.5-11.5, and the ammonia concentration during the reaction is 0.5-2 g / L.
[0031] In an optional embodiment, the flow rate of adding the second nickel-manganese mixed salt solution into the reactor is 4-8 L / h.
[0032] In a third aspect, the present invention provides a lithium-rich manganese-based positive electrode material, wherein the lithium-rich manganese-based positive electrode material is prepared by mixing and sintering the lithium-rich manganese-based positive electrode precursor material described in the first aspect with a lithium source.
[0033] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a positive electrode plate, and the positive electrode plate comprises the lithium-rich manganese-based positive electrode material as described in the third aspect.
[0034] The present invention has the following beneficial effects: (1) The lithium-rich manganese-based positive electrode precursor material provided by the present invention is a secondary particle formed by the agglomeration of primary particles, and has a stable "loose inside and tight outside" structure, that is, the core of the material is loose and the shell is dense, and the positive electrode material prepared therefrom can also inherit the structural characteristics of the precursor. The loose core has a porous structure formed by the staggered arrangement of flaky primary particles, and the structure has a high porosity, which is conducive to the diffusion of lithium ions; the shell is relatively dense and doped with boron. The introduction of borate can change the growth orientation of the precursor material grains, thereby improving the morphology of the shell primary particles. During the reaction, the shell primary particles will gradually thicken into a plate shape and radially distribute along the radial surface perpendicular to the core surface to form a dense shell. The shell structure can not only strengthen the core of the precursor material, increase the mechanical strength and structural stability of the precursor material, but also inhibit the generation of side reactions between the positive electrode material prepared therefrom and the electrolyte, thereby improving the cycle life and charge and discharge performance of the lithium battery.
[0035] (2) The preparation method provided by the present invention combines a continuous method with an intermittent method. The continuous method is used to prepare the loose inner core. During the reaction process, feeding and discharging are carried out simultaneously, and the stability of the liquid level in the kettle is maintained by overflow. When the inner core surface is coated with a dense shell layer, an intermittent method is used. During the reaction process, the clear liquid in the kettle is discharged by concentrating the inner core with a concentrator, thereby increasing the solid content in the reactor. The combination of the continuous method and the intermittent method can effectively regulate the seed morphology of the lithium-manganese-rich precursor material. The obtained precursor material has good particle consistency and batch stability, and the process is simple, the synthesis is highly controllable, and large-scale production is easy to achieve.
[0036] Other aspects will be apparent upon reading and understanding the drawings and detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings are used to provide further understanding of the technical solution of this article and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of this article and do not constitute a limitation on the technical solution of this article.
[0038] Figure 1 The SEM image (a) and SEM cross-sectional image (b) of the lithium-rich manganese-based positive electrode precursor material prepared in Example 5; Figure 2 This is a SEM image of the lithium-rich manganese-based positive electrode precursor material prepared in Comparative Example 1; Figure 3 This is the SEM image of the lithium-rich manganese-based positive electrode precursor material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present disclosure and should not be regarded as specific limitations of the present invention.
[0040] It should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.
[0041] The technical terms "first", "second", etc. in the present invention are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0042] The reference to "embodiment" in the present invention means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0043] The technical term "and / or" in the present invention is only a description of the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone.
[0044] In the present invention, the character " / " generally indicates that the objects before and after the association are in an "or" relationship, and the meaning of "at least one" refers to one or more than one.
[0045] In the first aspect, the present invention provides a lithium-rich manganese-based positive electrode precursor material, which includes a core and a shell layer on the surface of the core; the core is formed by an alternating arrangement of flaky primary particles, and the shell layer is formed by plate-like primary particles arranged radially along a radial surface perpendicular to the surface of the core.
[0046] The morphology and structure of the lithium-rich manganese-based positive electrode precursor material of the present invention are as shown in the attached specification. Figure 1 As shown in (b), the flaky primary particles are randomly distributed and staggered and agglomerated to form a loose core. The radial surfaces of the plate-like primary particles are perpendicular to the surface of the core ball and radially distributed and agglomerated to form a dense and compact shell. The precursor material as a whole has a core-shell structure with a loose core and a tight shell. The loose core structure is conducive to the diffusion and migration of lithium ions, and the tight shell can serve as a protective layer to increase the structural stability of the precursor material, avoiding the structural collapse of the positive electrode material prepared therefrom due to volume expansion during the charge and discharge process, which is beneficial to improving the cycle stability of the positive electrode material.
[0047] In some embodiments, the core of the lithium-rich manganese-based positive electrode precursor material is nickel manganese hydroxide, with a chemical formula of Ni x Mn y (OH)2, the shell is a composite of nickel manganese hydroxide and nickel manganese borate, the chemical formula of the nickel manganese borate is (Ni x Mn y )3(BO3)2, where 0.2≤x≤0.4, 0.6≤y≤0.8, x+y=1.
[0048] In some embodiments, the porosity of the inner core of the lithium-rich manganese-based positive electrode precursor material is greater than the porosity of the shell layer.
[0049] In some embodiments, the thickness of the flaky primary particles in the lithium-rich manganese-based positive electrode precursor material is 0.04-0.11 μm, and the thickness of the plate-like primary particles is 0.1-0.3 μm.
[0050] In some embodiments, the porosity of the core in the lithium-rich manganese-based positive electrode precursor material is 8%-13%, and the porosity of the shell is 1%-5%.
[0051] In some embodiments, the diameter of the core in the lithium-rich manganese-based positive electrode precursor material is 1.5-4 μm, and the thickness of the shell is 1-3 μm.
[0052] In some embodiments, the median particle size Dv50 of the lithium-rich manganese-based positive electrode precursor material is 3-7 μm.
[0053] In some embodiments, the mass percentage of boron element in the lithium-rich manganese-based positive electrode precursor material is 0.03%-0.2%.
[0054] In some embodiments, the tap density of the lithium-rich manganese-based positive electrode precursor material is 1.5-2.0 g / cm 3 .
[0055] In some embodiments, the specific surface area of the lithium-rich manganese-based positive electrode precursor material is 12-20 m 2 / g.
[0056] The primary particle thickness, porosity, particle median diameter, boron content, tap density and specific surface area of the lithium-rich manganese-based positive electrode precursor material of the present invention are within an appropriate range, so that the lithium-rich manganese-based positive electrode material can obtain relatively excellent electrochemical performance.
[0057] In a second aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode precursor material, the preparation method comprising: preparing a first slurry containing nickel manganese hydroxide particles; preparing a mixed solution containing nickel, manganese and boron; The mixed solution, the first precipitant solution and the first ammonia water are added in parallel to the reactor containing the first slurry to carry out a first co-precipitation reaction, and the concentrator is turned on for concentration. When the particle size Dv50 of the particles in the reactor reaches 3-7 μm, the liquid feeding is stopped to obtain a second slurry; the second slurry is subjected to solid-liquid separation, washing, drying and sieving to obtain a lithium-rich manganese-based positive electrode precursor material.
[0058] In some embodiments, the mixed solution is obtained by mixing a first nickel-manganese mixed salt solution with a boron source solution, and the concentration of the boron source solution is 0.1-2 mol / L, for example, it can be 0.1 mol / L, 0.8 mol / L, or 2 mol / L, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0059] In some embodiments, the mass of the boron source in the mixed solution is 0.2%-1% of the theoretical yield of nickel manganese hydroxide in the lithium-rich manganese-based positive electrode precursor material, for example, it can be 0.2%, 0.4% or 1%, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0060] In some embodiments, before the first coprecipitation reaction is performed, sulfuric acid solution (1 mol / L) and first ammonia water are added to a reactor containing the first slurry for adjustment to control the pH value and ammonia concentration of the slurry in the reactor to reach target values.
[0061] In some embodiments, the temperature of the first coprecipitation reaction is 45-60°C, for example, 45°C, 50°C or 60°C, the reaction pH is 9.5-10.5, for example, 9.5, 10 or 10.5, and the ammonia concentration during the reaction is 1.5-4.5 g / L, for example, 1.5 g / L, 3.0 g / L or 4.5 g / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0062] In some embodiments, continuous stirring is required during the first coprecipitation reaction, and the stirring speed is 300-450 r / min, for example, 300 r / min, 420 r / min or 450 r / min, but is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0063] In the first coprecipitation reaction, i.e., the shell growth stage, the ammonia concentration and reaction temperature during the reaction are relatively high. The high ammonia concentration can reduce the saturation of metal ions in the reaction solution, so that the number of free metal ions in the reaction system is reduced, and the growth rate of the primary particles of the shell is slowed down. With the introduction of borate ions, the orientation of the growth of the primary particles is changed, and finally thick plate-like primary particles are obtained; the higher reaction temperature can not only make the coprecipitation reaction run stably, but also make the primary particles orderly embedded in the secondary particles, thereby forming lithium-rich manganese-based positive electrode precursor particles with uniform morphology. If the reaction temperature and the ammonia concentration of the reaction solution during the first coprecipitation reaction are too low, the thickness of the primary particles of the shell will become thinner and the distribution will be looser, making it difficult to form a dense shell.
[0064] In some embodiments, the flow rate of adding the mixed solution to the reactor is 2-4 L / h, for example, it can be 2 L / h, 3 L / h or 4 L / h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0065] In some embodiments, the first coprecipitation reaction process includes maintaining the pH of the reaction system by adjusting the flow rate of the first precipitant solution, and maintaining the ammonia concentration of the reaction system by adjusting the flow rate of the first ammonia water.
[0066] In some embodiments, the preparation step of the first slurry includes introducing an inert gas into a reactor containing pure water and starting stirring, adding a second nickel-manganese mixed salt solution, a second precipitant solution, and a second ammonia water into the reactor in parallel to perform a second co-precipitation reaction, and stopping the liquid feeding when the particle size Dv50 of the slurry particles in the reactor reaches 1.5-4 μm to obtain a first slurry containing nickel-manganese hydroxide particles.
[0067] In some embodiments, the molar concentration of metal elements in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution is 0.5-2.5 mol / L, for example, it can be 0.5 mol / L, 2.0 mol / L or 2.5 mol / L, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0068] In some embodiments, the molar ratio of nickel element to manganese element in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution is (0.2-0.4):(0.6-0.8), for example, it can be 0.2:0.8, 0.35:0.65 or 0.4:0.6, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0069] In some embodiments, the molar concentration of the first precipitant solution and the second precipitant solution is 6-12 mol / L, for example, 6 mol / L, 10 mol / L and 12 mol / L, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0070] In some embodiments, the molar concentration of the first ammonia water and the second ammonia water is 0.5-2 mol / L, for example, 0.5 mol / L, 1.5 mol / L or 2 mol / L, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0071] In some embodiments, the inert gas is nitrogen, and the nitrogen flow rate is 5-30 L / min, for example, it can be 5 L / min, 10 L / min or 30 L / min, and the stirring speed is 450-600 r / min, for example, it can be 450 r / min, 550 r / min or 600 r / min, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0072] In some embodiments, before the second coprecipitation reaction is performed, a second precipitant solution and a second ammonia water are added to a reaction kettle containing pure water for adjustment to control the pH value and ammonia concentration of the bottom liquid in the kettle to reach target values.
[0073] In some embodiments, the reaction temperature of the second coprecipitation reaction is 35-45°C, for example, 35°C, 40°C or 45°C, the reaction pH is 10.5-11.5, for example, 10.5, 11.0 or 11.5, and the ammonia concentration during the reaction is 0.5-2g / L, for example, 0.5g / L, 1g / L or 2g / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0074] In some embodiments, during the second coprecipitation reaction, feeding and discharging need to be performed simultaneously, and the liquid level in the reactor is kept constant by overflow.
[0075] In the second coprecipitation reaction, i.e., the inner core growth stage, the reaction pH range is controlled near the crystallization line of nickel manganese hydroxide, which effectively inhibits the growth of the inner core primary particles; compared with the first coprecipitation reaction, the reaction liquid ammonia concentration and reaction temperature of the second coprecipitation reaction are relatively low, and the complexing effect of the complexing agent on the metal ions in the system is relatively weak, which provides better reaction conditions for the homogeneous nucleation of nickel manganese hydroxide crystals, is conducive to the growth of crystal nuclei, and can inhibit the continuous thickening of the formed crystal nuclei, and finally obtain a large amount of thin inner core flaky primary particles, which are staggered and disorderly distributed to present a loose structure. If the reaction temperature and the reaction liquid ammonia concentration in the second coprecipitation reaction are too high, the complexing effect of the complexing agent on the metal ions in the system is relatively strong, which will make the nucleation reaction rate of the crystal too fast, and the thickness of the generated inner core primary particles is thicker and the uniformity is poor, which is not conducive to the formation of a loose inner core.
[0076] In some embodiments, the flow rate of adding the second nickel-manganese mixed salt solution to the reactor is 4-8 L / h, for example, it can be 4 L / h, 6 L / h or 8 L / h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0077] In some embodiments, the second co-precipitation reaction process includes maintaining the pH of the reaction system by adjusting the flow rate of the second precipitant solution, and maintaining the ammonia concentration of the reaction system by adjusting the flow rate of the second ammonia water.
[0078] In a third aspect, the present invention provides a lithium-rich manganese-based positive electrode material, wherein the lithium-rich manganese-based positive electrode material is prepared by mixing and sintering the lithium-rich manganese-based positive electrode precursor material described in the first aspect with a lithium source.
[0079] In a fourth aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The positive electrode sheet comprises a lithium-rich manganese-based positive electrode material as described in the third aspect. The method for preparing the lithium-ion battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator, and the negative electrode sheet can each be a sheet body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium-ion battery.
[0080] Specifically, the features and performances of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0081] Example 1 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 10.17%, and the porosity of the shell is 2.59%; the thickness of the core flaky primary particles in the precursor material is 0.08 μm, and the thickness of the shell plate-like primary particles is 0.20 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: S1. Dissolve nickel sulfate and manganese sulfate in deionized water at a molar ratio of Ni:Mn=0.35:0.65 to prepare first and second nickel-manganese mixed salt solutions with a molar concentration of 2.0 mol / L; prepare first and second sodium hydroxide solutions with a molar concentration of 10 mol / L; prepare first and second ammonia solutions with a molar concentration of 2 mol / L; S2. Add pure water to a 100L reactor equipped with a temperature-controlled water bath jacket, a stirring paddle and a pH detection probe until the pure water bottom liquid submerges all the stirring paddles of the reactor (the volume of pure water is about 40% of the volume of the reactor). After heating to 40°C, introduce nitrogen at a flow rate of 10L / min into the sealed reactor, turn on the stirring paddle at the same time, set the speed to 600r / min, and introduce the second ammonia water and the second sodium hydroxide solution into the reactor until the ammonia concentration of the bottom liquid in the reactor reaches 1.0g / L and the pH value reaches 11.0; then, use a precision metering pump with a flow rate of 6L / h of a second nickel-manganese mixed salt solution, a second sodium hydroxide solution, and a second ammonia water are added to the reactor in parallel to carry out a second coprecipitation reaction, during the reaction, the liquid level in the reactor is kept stable by overflow, and the ammonia concentration of the reaction system is maintained at 1.0 g / L and the pH is maintained at 11.0 by controlling the flow rates of the second ammonia water and the second sodium hydroxide solution, during the reaction, samples are taken from the reactor every 1.5 hours, and the particle size of the taken particles is tested by a laser particle size analyzer, and the liquid is stopped when the particle size Dv50 of the slurry particles in the reactor reaches 2.5 μm, thereby obtaining a first slurry containing nickel-manganese hydroxide particles; S3, 0.8 mol / L boric acid solution and the first nickel-manganese mixed salt solution are mixed to obtain a mixed solution (the mass of the boron source in the mixed solution is 0.4% of the theoretical yield of nickel-manganese hydroxide); the reactor is heated to 50°C, the speed of the stirring paddle is adjusted to 420 r / min, and 1 mol / L sulfuric acid solution and the first ammonia water are introduced into the reactor until the pH value of the slurry in the reactor reaches 9.5 and the ammonia concentration reaches 3.0 g / L; a precision metering pump is used to add the mixed solution, the first sodium hydroxide solution and the first ammonia water at a flow rate of 4 L / h into the reactor in parallel for a first coprecipitation reaction, and samples are taken from the reactor every 1.5 h during the reaction, and the samples are analyzed using a laser particle size analyzer. The particle size of the particles taken was tested. As the feeding continued, a concentrator was used for concentration, and the liquid level was maintained near the overflow port. During the reaction, the ammonia concentration of the reaction system was maintained at 3.0 g / L and the pH was maintained at 9.5 by controlling the flow rates of the first ammonia water and the first sodium hydroxide solution. When the particle size Dv50 of the particles in the kettle reached 4.5 μm, the liquid feeding was stopped to obtain a second slurry. The second slurry was dried with a centrifuge, and then alkaline washed with a dilute sodium hydroxide solution (50 L, 0.8 mol / L) and washed with pure water (350 L). The washed material was then placed in a 120°C blast oven for drying, and then passed through a 300-mesh sieve to obtain a lithium-rich manganese-based positive electrode precursor material.
[0082] Example 2 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 11.55%, and the porosity of the shell is 3.91%; the thickness of the core flaky primary particles in the precursor material is 0.07 μm, and the thickness of the shell plate-like primary particles is 0.17 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: S1. Dissolve nickel sulfate and manganese sulfate in deionized water at a molar ratio of Ni:Mn=0.2:0.8 to prepare first and second nickel-manganese mixed salt solutions with a molar concentration of 0.5 mol / L; prepare first and second sodium hydroxide solutions with a molar concentration of 6 mol / L; prepare first and second ammonia solutions with a molar concentration of 0.5 mol / L; S2. Add pure water to a 100L reactor equipped with a temperature-controlled water bath jacket, a stirring paddle and a pH detection probe until the pure water bottom liquid submerges all the stirring paddles of the reactor (the volume of pure water is about 40% of the volume of the reactor). After heating to 35°C, introduce nitrogen at a flow rate of 5L / min into the sealed reactor, turn on the stirring paddle at the same time, set the speed to 450r / min, and introduce the second ammonia water and the second sodium hydroxide solution into the reactor until the ammonia concentration of the bottom liquid in the reactor reaches 0.5g / L and the pH value reaches 10.5; then, use a precision metering pump with a flow rate of 4L / h, a second nickel-manganese mixed solution, a second sodium hydroxide solution, and a second ammonia water are added to the reactor in parallel to carry out a second coprecipitation reaction, the liquid level in the reactor is kept stable by overflow during the reaction, and the ammonia concentration of the reaction system is maintained at 0.5 g / L and the pH is maintained at 10.5 by controlling the flow rates of the second ammonia water and the second sodium hydroxide solution, sampling is performed from the reactor every 1.5 hours during the reaction, and the particle size of the particles taken is tested by a laser particle size analyzer, and the liquid feeding is stopped when the particle size Dv50 of the slurry particles in the reactor reaches 1.5 μm, thereby obtaining a first slurry containing nickel-manganese hydroxide particles; S3, 0.1 mol / L boric acid solution and the first nickel-manganese mixed salt solution are mixed to obtain a mixed solution (the mass of the boron source in the mixed solution is 1.0% of the theoretical yield of nickel-manganese hydroxide); the reactor is heated to 45°C, the speed of the stirring paddle is adjusted to 300r / min, and 1 mol / L sulfuric acid solution and the first ammonia water are introduced into the reactor until the pH value of the slurry in the reactor reaches 10 and the ammonia concentration reaches 1.5g / L; a precision metering pump is used to add the mixed solution, the first sodium hydroxide solution and the first ammonia water at a flow rate of 4L / h into the reactor in parallel for a first coprecipitation reaction, and samples are taken from the reactor every 1.5h during the reaction, and the samples are analyzed by a laser particle size analyzer. The particle size of the particles taken was tested. As the feeding continued, a concentrator was used to concentrate the particles, and the liquid level was maintained near the overflow port. During the reaction, the flow rates of the first ammonia water and the first sodium hydroxide solution were controlled to maintain the ammonia concentration of the reaction system at 1.5 g / L and the pH at 10. When the particle size Dv50 of the particles in the kettle reached 3.0 μm, the liquid feeding was stopped to obtain a second slurry. The second slurry was dried with a centrifuge, and then alkaline washed with a dilute sodium hydroxide solution (50 L, 0.8 mol / L) and washed with pure water (350 L). The washed material was then dried in a 120°C blast oven and then sieved through a 300-mesh sieve to obtain a lithium-rich manganese-based positive electrode precursor material.
[0083] Example 3 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 12.83%, and the porosity of the shell is 4.67%; the thickness of the core flaky primary particles in the precursor material is 0.05 μm, and the thickness of the shell plate-like primary particles is 0.13 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: S1. Dissolve nickel sulfate and manganese sulfate in deionized water at a molar ratio of Ni:Mn=0.4:0.6 to prepare first and second nickel-manganese mixed salt solutions with a molar concentration of 2.5 mol / L; prepare first and second sodium hydroxide solutions with a molar concentration of 12 mol / L; prepare first and second ammonia solutions with a molar concentration of 1.5 mol / L; S2. Add pure water to a 100L reactor equipped with a temperature-controlled water bath jacket, a stirring paddle and a pH detection probe until the pure water bottom liquid submerges all the stirring paddles of the reactor (the volume of pure water is about 40% of the volume of the reactor). After heating to 45°C, introduce nitrogen at a flow rate of 30L / min into the sealed reactor, turn on the stirring paddle at the same time, set the speed to 550r / min, and introduce the second ammonia water and the second sodium hydroxide solution into the reactor until the ammonia concentration of the bottom liquid in the reactor reaches 2.0g / L and the pH value reaches 11.5; then, use a precision metering pump with a flow rate of 8L / h, a second nickel-manganese mixed salt solution, a second sodium hydroxide solution, and a second ammonia water are added to the reactor in parallel to carry out a second coprecipitation reaction, during the reaction, the liquid level in the reactor is kept stable by overflow, and the ammonia concentration of the reaction system is maintained at 2.0 g / L and the pH is maintained at 11.5 by controlling the flow rates of the second ammonia water and the second sodium hydroxide solution, sampling is performed from the reactor every 1.5 hours during the reaction, and the particle size of the particles taken is tested by a laser particle size analyzer, and the liquid feeding is stopped when the particle size Dv50 of the slurry particles in the reactor reaches 4.0 μm, thereby obtaining a first slurry containing nickel-manganese hydroxide particles; S3, mixing 2 mol / L boric acid solution with the first nickel-manganese mixed salt solution to obtain a mixed solution (the mass of the boron source in the mixed solution is 0.2% of the theoretical yield of nickel-manganese hydroxide); heating the reactor to 60°C, adjusting the speed of the stirring paddle to 450 r / min, and introducing 1 mol / L sulfuric acid solution and the first ammonia water into the reactor until the pH value of the slurry in the reactor reaches 10.5 and the ammonia concentration reaches 4.5 g / L; using a precision metering pump, adding the mixed solution, the first sodium hydroxide solution and the first ammonia water at a flow rate of 3 L / h into the reactor in parallel to carry out a first coprecipitation reaction, sampling from the reactor every 1.5 h during the reaction, and measuring the concentration of the mixed solution with a laser particle size analyzer. The particle size of the particles was tested. As the feeding continued, the particles were concentrated using a concentrator and the liquid level was maintained near the overflow port. During the reaction, the ammonia concentration of the reaction system was maintained at 4.5 g / L and the pH was maintained at 10.5 by controlling the flow rates of the first ammonia water and the first sodium hydroxide solution. When the particle size Dv50 of the particles in the kettle reached 7.0 μm, the liquid feeding was stopped to obtain a second slurry. The second slurry was dried using a centrifuge, and then alkaline washed with a dilute sodium hydroxide solution (50 L, 0.8 mol / L) and washed with pure water (350 L). The washed material was then dried in a 120°C blast oven and then sieved through a 300-mesh sieve to obtain a lithium-rich manganese-based positive electrode precursor material.
[0084] Example 4 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 10.23%, and the porosity of the shell is 2.37%; the thickness of the core flaky primary particles in the precursor material is 0.06 μm, and the thickness of the shell plate-like primary particles is 0.19 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the ammonia concentration of the bottom liquid in the kettle in step S2 is changed to 0.5 g / L, and the liquid feeding is stopped when the particle size Dv50 of the slurry particles in the kettle reaches 3 μm; the ammonia concentration of the slurry in step S3 is changed to 1.5 g / L, and the liquid feeding is stopped when the particle size Dv50 of the particles in the kettle reaches 4.5 μm; the other steps remain unchanged.
[0085] Example 5 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 10.51%, and the porosity of the shell is 3.34%; the thickness of the core flaky primary particles in the precursor material is 0.09 μm, and the thickness of the shell plate-like primary particles is 0.18 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the ammonia concentration of the bottom liquid in the kettle in step S2 is changed to 2.0 g / L, and the liquid feeding is stopped when the particle size Dv50 of the slurry particles in the kettle reaches 3 μm; the ammonia concentration of the slurry in step S3 is changed to 3.0 g / L, and the liquid feeding is stopped when the particle size Dv50 of the particles in the kettle reaches 5 μm; the other steps remain unchanged.
[0086] Example 6 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 8.37%, and the porosity of the shell is 1.97%; the thickness of the core flaky primary particles in the precursor material is 0.10 μm, and the thickness of the shell plate-like primary particles is 0.23 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the temperature of the second coprecipitation reaction in step S2 was changed to 45° C., and the ammonia concentration of the bottom liquid in the kettle was changed to 2.0 g / L, and the other steps remained unchanged.
[0087] Example 7 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 10.33%, and the porosity of the shell is 2.54%; the thickness of the core flaky primary particles in the precursor material is 0.06 μm, and the thickness of the shell plate-like primary particles is 0.18 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the temperature of the second coprecipitation reaction in step S2 was changed to 35° C., and the ammonia concentration of the bottom liquid in the kettle was changed to 0.5 g / L, and the other steps remained unchanged.
[0088] Example 8 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 9.85%, and the porosity of the shell is 3.05%; the thickness of the core flaky primary particles in the precursor material is 0.07 μm, and the thickness of the shell plate-like primary particles is 0.14 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the temperature of the first coprecipitation reaction in step S3 was changed to 45° C., and the ammonia concentration of the bottom liquid in the kettle was changed to 1.5 g / L, and the other steps remained unchanged.
[0089] Example 9 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 9.78%, and the porosity of the shell is 2.86%; the thickness of the core flaky primary particles in the precursor material is 0.07 μm, and the thickness of the shell plate-like primary particles is 0.22 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the temperature of the first coprecipitation reaction in step S3 was changed to 60° C., and the ammonia concentration of the bottom liquid in the kettle was changed to 4.5 g / L, and the other steps remained unchanged.
[0090] Example 10 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 9.68%, and the porosity of the shell is 3.07%; the thickness of the core flaky primary particles in the precursor material is 0.08 μm, and the thickness of the shell plate-like primary particles is 0.17 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the mass of the boron source in the mixed solution in step S3 is changed to 0.2% of the theoretical yield of nickel manganese hydroxide, and the other steps remain unchanged.
[0091] Embodiment 11 This embodiment provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 9.91%, and the porosity of the shell is 1.55%; the thickness of the core flaky primary particles in the precursor material is 0.07 μm, and the thickness of the shell plate-like primary particles is 0.27 μm. The preparation method of the lithium-rich manganese-based positive electrode precursor material is: Compared with Example 1, the mass of the boron source in the mixed solution in step S3 is changed to 1.0% of the theoretical yield of nickel manganese hydroxide, and the other steps remain unchanged.
[0092] Comparative Example 1 This comparative example provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 12.77%, and the porosity of the shell is 5.37%; the thickness of the core flaky primary particles in the precursor material is 0.04 μm, and the thickness of the shell plate-like primary particles is 0.09 μm.
[0093] Compared with Example 5, in step S3, sulfuric acid solution is not introduced into the reactor to adjust the pH of the slurry in the reactor before the first coprecipitation reaction, but the pH of the second coprecipitation reaction stage is maintained. During the first coprecipitation reaction, the pH of the slurry in the reactor is adjusted down by 0.1 every 1 hour until it reaches 9.5 and maintained until the end of the reaction; during the first coprecipitation reaction, the first nickel-manganese mixed salt solution, the first sodium hydroxide solution and the first ammonia water are added to the reactor in parallel, and the other steps are unchanged. (No doping with boron source) Comparative Example 2 This comparative example provides a lithium-rich manganese-based positive electrode precursor material, wherein the porosity of the core of the precursor material is 5.57%, and the porosity of the shell is 2.97%; the thickness of the core flaky primary particles in the precursor material is 0.12 μm, and the thickness of the shell plate-like primary particles is 0.43 μm.
[0094] Compared with Example 5, the temperature of the second coprecipitation reaction in step S2 is 50°C, and the ammonia concentration of the bottom liquid in the kettle is 4 g / L, the temperature of the first coprecipitation reaction in step S3 is 50°C, and the ammonia concentration of the bottom liquid slurry in the kettle is 4 g / L, the mass of the boron source in the mixed solution is 0.4% of the theoretical yield of nickel manganese hydroxide, and the other steps do not change.
[0095] The primary particle thickness and porosity of the lithium-rich manganese-based positive electrode precursor materials prepared in Examples 1 to 11 and Comparative Examples 1 to 2 were measured by the following method: the primary particle thickness was measured by analyzing the SEM images of the corresponding samples using Nano Measurer software; the porosity was measured by analyzing the SEM images of the corresponding samples using ImageJ software.
[0096] The element content, specific surface area, tap density and electrochemical performance of the lithium-rich manganese-based positive electrode precursor materials prepared in Examples 1 to 11 and Comparative Examples 1 to 2 were tested, specifically comprising the following steps: 1. Element content detection: Inductively coupled plasma emission spectrometer.
[0097] 2. Specific surface area test (BET): specific surface area analyzer.
[0098] 3. Tap density test (TD): Lester tap density meter.
[0099] 4. Electrochemical performance test: (1) Preparation of lithium-rich manganese-based positive electrode materials The obtained lithium-rich manganese-based positive electrode precursor material is mechanically mixed with lithium hydroxide (the molar ratio of the metal element in the precursor material to the lithium element in the lithium hydroxide is 1:1.05), placed in a muffle furnace, and sintered at a high temperature of 800-1100°C for 15-30h to finally obtain a lithium-rich manganese-based positive electrode material.
[0100] (2) Preparation of button cells The prepared lithium-rich manganese-based cathode material was mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as the solvent. The mixture was stirred in a small beaker at a speed of 800r / min for 2h to obtain a slurry. The slurry was coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 105°C for 4h. After punching into a pole piece with a diameter of 12mm, it was assembled into a CR2032 button battery in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm. The battery uses a pure metal lithium sheet with a diameter of 16 mm and a thickness of 0.5 mm as the negative electrode, a porous polyethylene membrane of model Celgard2300 with a diameter of 18 mm as the separator, and the electrolyte is 1 mol / L lithium hexafluorophosphate-ethylene carbonate: dimethyl carbonate (LiPF6-EC:DMC, the volume ratio of EC and DMC is 1:1).
[0101] (3) Electrochemical performance test The assembled button cell was subjected to electrochemical performance testing within the charge and discharge voltage range of 2.0-4.6V.
[0102] The test results are shown in Table 1-2.
[0103] Table 1
[0104] Table 2
[0105] In the attached figure: Figure 1 This is a SEM image of the lithium-rich manganese-based positive electrode precursor material prepared in Example 5, in which the flaky primary particles are randomly distributed and staggered and agglomerated to form a loose core ( Figure 1 (b) The plate-like primary particles are radially distributed along the radial surface perpendicular to the surface of the inner core and agglomerated to form a dense and compact shell ( Figure 1 (a)-(b)). Figure 2 This is an SEM image of the lithium-rich manganese-based positive electrode precursor material prepared in Comparative Example 1. In the image, the primary particles of the shell layer are flaky, and the distribution after agglomeration is relatively loose and not compact. There are also detached flaky primary particles on the surface of the shell layer. Figure 3 This is a SEM image of the lithium-rich manganese-based positive electrode precursor material prepared in Comparative Example 2. In the image, the primary particles of the shell layer are mostly block-shaped and uneven in thickness, and are densely distributed after agglomeration.
[0106] Table 1-2: From the analysis of Examples 1-11, it can be obtained that the lithium-rich manganese-based positive electrode precursor material of the present invention has relatively excellent specific surface area and tap density, and the positive electrode material prepared therefrom has high discharge specific capacity and cycle capacity residual rate, indicating that the positive electrode material has good electrochemical performance and also maintains high structural stability during the cycle process. This may be due to the positive electrode material inheriting the excellent physical and chemical properties of the lithium-rich manganese-based positive electrode precursor material and the "loose inside and tight outside" stable morphological structure.
[0107] From the analysis of Example 1, Examples 6-7 and Comparative Example 2, it can be obtained that in the preparation process of the lithium-rich manganese-based positive electrode precursor material of the present invention, the lower reaction temperature and ammonia concentration in the second coprecipitation reaction can provide better reaction conditions for the homogeneous nucleation of the nickel manganese hydroxide core crystals, so that the formed core primary particles are uniform and thin. In the subsequent mixed sintering process with the lithium source, the core primary particles of this structure can be fully lithiated, which is conducive to the electrochemical performance of the positive electrode material during the charge and discharge process. At the same time, due to the good uniformity of the core primary particles, the stress between the particles is not easy to accumulate, and the generated secondary particles have high structural strength, which makes the cycle capacity retention rate of the positive electrode material advantageous; while higher reaction temperature and ammonia concentration will make the generated core primary particles thicker and the uniformity deteriorate. The agglomerated secondary particles are prone to stress accumulation during the charge and discharge process, resulting in particle breakage, which is not conducive to the improvement of the electrochemical performance of the positive electrode material and the maintenance of the cycle stability.
[0108] From the analysis of Example 1 and Examples 8-9, it can be concluded that in the preparation process of the lithium-rich manganese-based positive electrode precursor material of the present invention, a higher reaction temperature in the first coprecipitation reaction can make the reaction run stably and promote the orderly agglomeration of primary particles, while a higher ammonia concentration can reduce the number of free metal ions in the reaction environment, slow down the growth rate of the shell primary particles, and thus form precursor particles with uniform morphology, so that the positive electrode material prepared therefrom has better electrochemical properties; while a lower reaction temperature and ammonia concentration will cause the thickness of the generated shell primary particles to become thinner and the distribution to be looser, which is not conducive to their agglomeration into a dense shell, thereby affecting the structural stability of the subsequently prepared positive electrode material and reducing its cycle performance. From the analysis of Example 1 and Examples 10-11, it can be concluded that during the preparation process of the lithium-rich manganese-based positive electrode precursor material of the present invention, doping with an appropriate amount of boron element will increase the structural stability of the precursor material, thereby enhancing the cycle performance of the subsequently prepared positive electrode material; while excessive boron doping will occupy too many structural gaps in the precursor material, thereby inhibiting the diffusion of lithium ions and reducing the electrochemical performance of the positive electrode material.
[0109] From the analysis of Example 5 and Comparative Example 1, it can be obtained that the lithium-rich manganese-based positive electrode precursor material prepared by the present invention adds boron element in the shell layer. Compared with Comparative Example 1, the introduction of borate can change the growth orientation of the precursor material grains, thereby improving the morphology of the shell primary particles. During the reaction, the shell primary particles will gradually thicken into a plate-like shape and be radially distributed along the radial surface perpendicular to the inner core surface and agglomerated into a tight shell layer. The shell structure can not only strengthen the inner core of the precursor material and make the structure of the precursor material more stable, but also inhibit the occurrence of side reactions between the positive electrode material prepared therefrom and the electrolyte, thereby further improving the electrochemical properties of the material.
[0110] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode precursor material, characterized in that: The lithium-rich manganese-based positive electrode precursor material includes a core and a shell layer on the surface of the core; the core is formed by staggered arrangement of flaky primary particles, and the shell layer is formed by plate-like primary particles arranged radially along a radial surface perpendicular to the surface of the core.
2. The lithium-rich manganese-based positive electrode precursor material according to claim 1, characterized in that: The core is nickel manganese hydroxide, the chemical formula of which is Ni x Mn y (OH)2, the shell is a composite of nickel manganese hydroxide and nickel manganese borate, the chemical formula of the nickel manganese borate is (Ni x Mn y )3(BO3)2, where 0.2≤x≤0.4, 0.6≤y≤0.8, x+y=1; And / or, the porosity of the inner core of the lithium-rich manganese-based positive electrode precursor material is greater than the porosity of the shell layer.
3. The lithium-rich manganese-based positive electrode precursor material according to claim 1 or 2, characterized in that: The thickness of the flaky primary particles is 0.04-0.11 μm, and the thickness of the plate-like primary particles is 0.1-0.3 μm; and / or, the porosity of the inner core is 8%-13%, and the porosity of the shell layer is 1%-5%; And / or, the diameter of the core is 1.5-4 μm, and the thickness of the shell is 1-3 μm; And / or, the median particle size Dv50 of the lithium-rich manganese-based positive electrode precursor material is 3-7 μm; And / or, the mass percentage of boron element in the lithium-rich manganese-based positive electrode precursor material is 0.03%-0.2%; And / or, the tap density of the lithium-rich manganese-based positive electrode precursor material is 1.5-2.0 g / cm 3 ; And / or, the specific surface area of the lithium-rich manganese-based positive electrode precursor material is 12-20m 2 / g.
4. A method for preparing the lithium-rich manganese-based positive electrode precursor material according to any one of claims 1 to 3, characterized in that: The following steps are involved: preparing a first slurry containing nickel manganese hydroxide particles; preparing a mixed solution containing nickel, manganese and boron; The mixed solution, the first precipitant solution and the first ammonia water are added in parallel to the reactor containing the first slurry to carry out a first co-precipitation reaction, and the concentrator is turned on for concentration. When the particle size Dv50 of the particles in the reactor reaches 3-7 μm, the liquid feeding is stopped to obtain a second slurry; the second slurry is subjected to solid-liquid separation, washing, drying and sieving to obtain a lithium-rich manganese-based positive electrode precursor material.
5. The method for preparing the lithium-rich manganese-based positive electrode precursor material according to claim 4, characterized in that: The mixed solution is obtained by mixing a first nickel-manganese mixed salt solution with a boron source solution, wherein the concentration of the boron source solution is 0.1-2 mol / L; the boron source comprises at least one of boric acid, sodium borate and ammonium borate; And / or, the mass of the boron source in the mixed solution is 0.2%-1% of the theoretical yield of nickel manganese hydroxide in the lithium-rich manganese-based positive electrode precursor material; and / or, the reaction temperature of the first coprecipitation reaction is 45-60° C., the reaction pH is 9.5-10.5, and the ammonia concentration during the reaction is 1.5-4.5 g / L; And / or, the mixed solution is added to the reactor at a flow rate of 2-4 L / h.
6. The method for preparing the lithium-rich manganese-based positive electrode precursor material according to claim 4, characterized in that: The preparation step of the first slurry includes introducing an inert gas into a reactor containing pure water and starting stirring, adding a second nickel-manganese mixed salt solution, a second precipitant solution and a second ammonia water into the reactor in parallel to carry out a second co-precipitation reaction, and stopping the liquid feeding when the particle size Dv50 of the particles in the reactor reaches 1.5-4μm to obtain a first slurry containing nickel-manganese hydroxide particles.
7. The method for preparing the lithium-rich manganese-based positive electrode precursor material according to any one of claims 4 to 6, characterized in that: The nickel salt in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution includes at least one of nickel sulfate, nickel chloride and nickel nitrate, and the manganese salt includes at least one of manganese sulfate, manganese chloride and manganese nitrate; and / or the molar concentration of the metal element in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution is 0.5-2.5 mol / L; And / or, the molar ratio of nickel element to manganese element in the first nickel-manganese mixed salt solution and the second nickel-manganese mixed salt solution is (0.2-0.4): (0.6-0.8); And / or, the first precipitant solution and the second precipitant solution are sodium hydroxide solution or potassium hydroxide solution with a molar concentration of 6-12 mol / L; And / or, the molar concentration of the first ammonia water and the second ammonia water is 0.5-2 mol / L.
8. The method for preparing the lithium-rich manganese-based positive electrode precursor material according to claim 6, characterized in that: The inert gas is nitrogen, and the nitrogen flow rate is 5-30L / min; and / or, the reaction temperature of the second coprecipitation reaction is 35-45° C., the reaction pH is 10.5-11.5, and the ammonia concentration during the reaction is 0.5-2 g / L; And / or, the flow rate of adding the second nickel-manganese mixed salt solution into the reactor is 4-8 L / h.
9. A lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material is prepared by mixing and sintering the lithium-rich manganese-based positive electrode precursor material according to any one of claims 1 to 3 and a lithium source.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode plate, and the positive electrode plate comprises the lithium-rich manganese-based positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Positive electrode active material precursor and preparation method thereof, and positive electrode active material
CN111370679A
Positive electrode active material precursor, preparation method thereof, and positive electrode active material
CN111653756A
Ternary precursor material, ternary positive electrode material, preparation method of ternary precursor material and preparation method of ternary positive electrode material, and lithium ion battery
CN115231625A
Cited By
Lithium-rich manganese-based precursor material as well as preparation method and application thereof
CN120887459A